FAKTOR-FAKTOR PEMICU KEPERCAYAAN ORGANISASI DAN KOMITMEN PROFESI PADA PEGAWAI KANTOR PELAYANAN PAJAK - Chuswatun Chasanah (The Indonesian Accounting Review, 2012)
The tax officials are required to fulfill the target determined by the government. In addition, the employees can experience high levels of role conflict when confronted by their work environment that emphasizes the achievement of the target. The purpose of this research is to find out the influence of Role Conflict and Job level on the Organizational Trust. Besides that, it also attempts to see the influence of Role Conflict and Job level towards the Professional Commitment. The primary data were taken from 12 tax offices and 102 tax officials in Surabaya by means of non probability sampling, concerning their opinions towards their organization and trust. The data analysis was done by means multiple regressions with dummy variable in SPSS version 16.00. From the data gathered, the analysis was done as well to find the results. It showed that Role Conflict and Job level influenced, significantly, the Organizational Trust. In addition, Role Conflict also influenced, significantly, the Professional Commitment, but Job level did not influence significantly the Professional Commitment.